Kondisi Sanitasi Lingkungan di Desa Sungai Sirah Kecamatan Pariaman Timur Kota Pariaman - Rozi, Muhammad Fakhrul; Afdhal, Afdhal (Lembaga Yasin AlSys, 2024)
Public health will become increasingly difficult along with the rapid growth of population in urban areas, which will give rise to various kinds of problems, one of which is the problem of environmental sanitation. The aim of this research is to determine the condition of environmental sanitation in Desa Sungai Sirah, which consists of aspects of the availability of clean water, MCK facilities (bathing, washing, toilet), rubbish disposal, and waste water disposal. This research was conducted on households in Desa Sungai Sirah. The sample for this research was taken from 35 households spread across the target area. Based on the research results, it can be concluded that: 1) The availability of clean water has met the criteria both in terms of source, availability, and physical condition of the clean water, 2) The condition of bathing, washing and toilet facilities (MCK) has met the criteria both in terms of ownership, quantity, floor condition, walls condition, roof condition, as well as in terms of location or position, 3) The condition of the waste disposal meets the criteria both in terms of the availability of rubbish dumps and there are cleaning staff who will transport the rubbish from house to house for disposal to the landfill, and 4) The condition of waste water disposal does not meet the criteria such as availability, condition of waste water drainage channels, and waste water disposal sites that do not meet the criteria.